2015
DOI: 10.1289/ehp.1408412
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit/Hyperactivity Disorder and Childhood Autism in Association with Prenatal Exposure to Perfluoroalkyl Substances: A Nested Case–Control Study in the Danish National Birth Cohort

Abstract: Background:Perfluoroalkyl substances (PFASs) are persistent pollutants found to be endocrine disruptive and neurotoxic in animals. Positive correlations between PFASs and neurobehavioral problems in children were reported in cross-sectional data, but findings from prospective studies are limited.Objectives:We investigated whether prenatal exposure to PFASs is associated with attention deficit/hyperactivity disorder (ADHD) or childhood autism in children.Methods:Among 83,389 mother–child pairs enrolled in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 48 publications
(67 reference statements)
5
108
2
1
Order By: Relevance
“…Consistent with the present findings, previous investigations showed no association between prenatal exposure to PFASs and child neurodevelopment (Fei and Olsen 2011; Liew et al 2015; Ode et al 2014; Stein et al 2013; Stein et al 2014). Previous studies of postnatal PFAS exposures and child neurodevelopment are inconsistent, but most were based on cross-sectional designs (Gump et al 2011; Hoffman et al 2010; Stein and Savitz 2011) with methodological limitations, such as unmeasured confounders and the potential for reverse causation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the present findings, previous investigations showed no association between prenatal exposure to PFASs and child neurodevelopment (Fei and Olsen 2011; Liew et al 2015; Ode et al 2014; Stein et al 2013; Stein et al 2014). Previous studies of postnatal PFAS exposures and child neurodevelopment are inconsistent, but most were based on cross-sectional designs (Gump et al 2011; Hoffman et al 2010; Stein and Savitz 2011) with methodological limitations, such as unmeasured confounders and the potential for reverse causation.…”
Section: Discussionsupporting
confidence: 93%
“…The maternal PFAS concentrations in our cohort were higher than previously reported levels in some other populations (Hoyer et al 2015), but comparable to those reported from Denmark (Liew et al 2015). The concentrations in children appeared to decrease over time for PFOS and somewhat for PFHxS, but tended to increase for other PFASs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…172 Several studies report protective or null associations between prenatal PFAS exposure and child neurobehavior. 64,165167,169,173 …”
Section: Perfluoroalkyl Substancesmentioning
confidence: 99%
“…3). Such chemicals may interfere with thyroid function (69), and they have also been considered risk factors for neurodevelopmental disorders in the offspring (70). Finally, psychiatric disease in the parents may introduce confounding (Fig.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%